Mix and manage: Cultivar mixtures can maintain yield under high wheat blast disease pressure - Krupnik, Timothy J.; Md. Harun-Or-Rashid; Dinabandhu Pandit; Islam, Rabiul; Hossain, Md. Khaled; Cunha Fernandes, Jose Mauricio; Roy, Krishna Kanta; Kabir, Muhammad Rezaul; Stuerz, Sabine; Singh, Pawan Kumar; Faruq, Golam (Elsevier, 2024)
Originating in South America, wheat blast disease has spread to both Asia and Africa and is considered a significant threat to food security. Bangladesh experienced the first outbreak of wheat blast outside of the Americas in 2016. Shortly thereafter, the blast-resistant variety BARI Gom 33 was released. Seeds of this variety are however not as widely available as required, although the disease threat remains. While varietal mixtures have been shown to mitigate some symptoms and yield losses associated with other fungal diseases in wheat, there is a complete research gap on this topic as it pertains to wheat blast. As such, we evaluated the potential of using BARI Gom 33 as a component of a variety mixture under high disease pressure in Bangladesh. During three cropping seasons, blast symptoms and yield were determined in a field experiment for the highly blast-susceptible variety BARI Gom 26, the moderately susceptible BARI Gom 30, the resistant BARI Gom 33, and seven mixture combinations of the three varieties using artificial inoculation to increase disease pressure. In addition to wheat blast, Bipolaris leaf blight (BpLB) symptoms were observed and evaluated. While yields of the susceptible varieties were severely affected by blast even after fungicide application, disease-inflicted yield loss without fungicide was only 15% for sole BARI Gom 33 and did not differ significantly from yield losses in BARI Gom 33 and BARI Gom 30 mixtures. Furthermore, in the mixture containing 67% BARI Gom 33 and 33% BARI Gom 30, blast incidence and severity were reduced by 25% and 16%, respectively, in comparison to weighted values in sole stands. Conversely, mixing varieties tended to increase the symptoms of BpLB. Under high wheat blast pressure, fungicide protection against blast was relatively weak, underscoring the importance of resistant varieties. Although variety mixtures did not increase yield, the yield advantage of BARI Gom 33 was maintained when its seeds were mixed with the less resistant BARI Gom 30. This study confirms recommendations that farmers should use BARI Gom 33 as a first line of defense against wheat blast in Bangladesh. Yet where farmers cannot access sufficient BARI Gom 33 seed for planting, our data suggest that agricultural extension services can recommend this variety with non-resistant cultivars as interim strategy without significant risk of yield loss.